Kinect em conjunto com o SRP-PHAT como solução de localização de fonte sonora - Seewald, Lucas Adams (Universidade do Vale do Rio dos Sinos, 2014)
This document presents an evaluation of Kinect together with SRP-PHAT as a Sound Source Localization solution. A functional prototype able to communicate with the device and perform SRP-PHAT was implemented in order to test the solution’s accuracy. The fundamentals of Sound Source Localization and it’s mathematical principles are reviewed, focusing specifically on the SRP-PHAT. Moving on to the Kinect device, some considerations are made about it’s components and limitations. Related work which resources to Kinects source localization capabilities is presented, followed by SRP-PHAT precision test results attained by different authors. Two experimental sets were conducted, one focused on the source signal properties and the other on measuring the proposed solutions quality. Performed experiments comprehend two dimensional and three dimensional localization, being a second Kinect needed for the latter. Implementation aspects concerning the software responsible for manipulating both Kinects and executing the localization algorithm are described along with experimental procedure details. Presented results show that the proposed solution can accurately point at the sources direction.
Keywords: SRP-PHAT; Localização de Fonte Sonora; Kinect; Sound source localization; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação